Survival rate of fixed space maintainers used in Dentistry. Systematic review and Meta-analysis - Heber Arbildo-Vega; Jeniffer Cantu-Oliva; Rubén Chumpitaz-Durand; José Agüero-Alva; Alfredo Rendón-Alvarado; Hernán Vásquez-Rodrigo (Universidad de Concepción., 2021)
Objective: To determine, through a systematic review and meta-analysis, the survival rate of fixed space maintainers used in Dentistry. Material and Methods: A literature search was carried out, following the guidelines of the PRISMA standards, until March 2020, in the biomedical databases: Pubmed, Embase, Scielo, Science Direct, Scopus, SIGLE, LILACS, Google Scholar and the Cochrane Central Registry of Clinical Trials. The selection criteria of the studies were defined as: clinical trials, without language restriction, up to 10 years old and that report the survival rate of fixed space maintainers used in dentistry. Study risk of bias was analyzed using the Cochrane Handbook of Systematic Reviews of Interventions. Results: The search strategy resulted in 159 articles, of which 10 were ultimately included for the present study. All included articles reported that the overall survival rate of the fixed space maintainers used in Dentistry was between 20% and 95%; the one with the highest survival rate is the crown and loop with 86.3%. When comparing the fiber-reinforced composite space maintainers with the band and loop it was observed that there is no difference between them; when comparing the crown and loop with the band and loop, a difference was observed, favoring the crown and loop. Conclusion: The reviewed literature suggests that the overall survival rate of fixed space maintainers used in dentistry ranges from 20 to 86.3% with a follow-up time of 6 to 18 months.